The FORMULATION AND EVALUATION O FORMULATION AND EVALUATION OF THE PREPARATION OF HAIR TONIC Ethanol Extract of Patchouli Leaves (Pogostemon cablin Benth.) TO OVERCOME HAIR LOSS - Bunga Rimta Barus; Linta Meliala (Jurnal Penelitian Farmasi & Herbal, 2022)
Nilam leaves contain flavonoids. flavonoids that have activity that can accelerate hair growth and prevent hair loss. The purpose of the study was to make a hair tonic preparation containing patchouli leaf extract and to determine the concentration of the best formula to treat hair loss. Hair tonic is made with nilam leaf extract at concentrations of 5%, 10%, 15%. The ingredients for making Hair Tonic include propylene glycol, propyl paraben, methyl paraben, menthol, sodium metabisulfite, 96% ethanol, Ol. Rosae, Aquades. The method of the study an experimental method with extraction by maceration for 5 days and remaceration for 2 days using 96% ethanol as solvent. Evaluation of Hair Tonic preparations includes homogeneity, pH, organoleptic, viscosity, irritation, preference, and hair growth effectiveness test. The effectiveness test on hair growth in rabbits was carried out on 5 rabbits with 5 treatment groups, namely, positive control group Hair Tonic nature, negative control group, 5% concentration group, 10% concentration group, and 15% concentration group. The analysis of the data on growth testing using One Way Anova. Hair growth data on day 12 were positive control 0.95 mm, negative control 0.03 mm, formula 1 (5%) 0.08 mm, formula 2 (10%) 0.13 mm, formula 3 (15%) 0.83mm. The best formula to treat hair loss is hair tonic with a concentration of 15% nilam leaf ethanol extract. It can be concluded that the greater the concentration of nilam leaf extract given to each treatment, the faster the hair growth.